Uso de planejamento experimental de misturas na otimização da pasta e no empacotamento de agregados para produção de CAA - Leite, Guilherme Urquisa (2016)
The self-compacting concrete (SCC) was created in the late 80s and since then has been treated as a great evolution in concrete technology. Many studies have been developed, such as: component materials, technical and economic feasibility and also mixture methods. The latter topic is an important step in the development of this type of concrete, since it must comply with specific performance in both the fresh and hardened states, performance is related to the proportion between the constituent materials. The use of a mixture experiments design (MED) seems to incorporate the assumptions necessary to understand the relationship between the proportion of the constituents and the SCC physical characteristics. Considering that the SCC is made of two phases (paste and aggregate), a MED was used in each one of them. The aggregate phase only required the use of a simplex-centroid design. On the paste phase, it was necessary to develop a distinct method, double pseudo-simplex (DPS). Results made it clear that the mix process of SCC, using MED methodology, made it possible to obtain a SCC with minimum experiments and amounts of materials. The use of this tool may be extremely relevant to mix SCC in a large scale, allowing the prediction of basic characteristics of production and securing a more effective planning and production control.